2011
DOI: 10.1016/j.jtcvs.2010.09.011
|View full text |Cite
|
Sign up to set email alerts
|

In an era of health reform: Defining cost differences in current esophageal cancer management strategies and assessing the cost of complications

Abstract: Costs vary significantly among treatment approaches: surgery alone costs 80% of chemotherapy and surgery, 71% of chemoradiotherapy and surgery, and 72% of chemoradiotherapy alone. Costs of tri-modality therapy and definitive chemoradiotherapy are similar. Especially in the absence of definitive evidence-based data, these costs should be a factor in the production of future national treatment guidelines. Decreasing costs requires future quality initiatives in esophageal cancer treatment that focus on minimizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Our results were compatible with previous randomized trials and population‐based studies, in that NCCRT was effective in improving survival . Our results were also consistent with previous studies in that NCCRT was associated with increased cost . Furthermore, to the best of our knowledge, our study is the first to provide an estimate of cost‐effectiveness of NCCRT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results were compatible with previous randomized trials and population‐based studies, in that NCCRT was effective in improving survival . Our results were also consistent with previous studies in that NCCRT was associated with increased cost . Furthermore, to the best of our knowledge, our study is the first to provide an estimate of cost‐effectiveness of NCCRT.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, neoadjuvant therapy (such as NCCRT) has been associated with improved survival for resectable esophageal cancer when compared to surgery, and may or may not increase the risk of postoperative morbidity . Neoadjuvant therapy is also associated with increased cost . However, there is a paucity of cost‐effectiveness analysis (CEA) regarding NCCRT in esophageal cancer, which is highly desirable in an era of increasing health care costs and the desire for affordable cancer care .…”
Section: Introductionmentioning
confidence: 99%
“…We showed that there is a statistically significant difference in total hospital costs for patients who developed major complications. Kuppusamy et al also showed a difference in costs between patients who developed complications and who did not develop complications undergoing esophageal resection [ 21 ]. However, the study population consisted of four small groups of 15 patients undergoing different treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The system tracks actual costs but has an 18-month delay until data are complete. That enabled us to examine specific actual costs in our different treatment groups [12].…”
Section: Methodsmentioning
confidence: 99%